Modulation of interleukin 1 beta gene expression by the immediate early genes of human cytomegalovirus. - Iwamoto, G K (1990)
The immediate early (IE) genes of human cytomegalovirus (HCMV) can be expressed in monocytes/macrophages and are known to regulate other viral genes. The purpose of these studies was to determine if HCMV IE gene products also modulate expression of a monocyte/macrophage-derived gene, interleukin 1 (IL-1) beta. Steady-state cell-derived IL-1 beta mRNA was increased in lipopolysaccharide (LPS)-stimulated THP-1 cells when transfected with the HCMV IE1 + 2 genes, when compared to cells transfected with a control DNA. LPS-stimulated THP-1 cells also exhibited approximately 30-fold higher IL-1 CAT activity when cotransfected with IE1 + 2 than was observed for the same cells cotransfected with IL-1 CAT and a control plasmid containing the IE promoter alone. LPS increased IL-1 CAT activity in the absence of HCMV genes only twofold. IE1, by itself, increased IL-1 CAT activity in LPS-stimulated cells, whereas, IE2, by itself, caused no change in IL-1 CAT activity. These studies show that the IE1 gene of HCMV can regulate IL-1 beta gene expression. The observations further suggest that some of the inflammatory processes associated with HCMV infection may be due to an effect of HCMV IE genes on cell-derived genes, such as the IL-1 beta gene.